EXPLORING LONG AND SHORT VOWELS SOUND IN ED SHEERAN'S SONG - Sri Mulyati (LPPM Universitas Bina Sarana Informatika, 2020)
Linguistics is a science study about the using of language and its provisions inside. Historically, linguistics comes from Latin language